2013
DOI: 10.1111/dmcn.12162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical tools to assess balance in children and adults with cerebral palsy: a systematic review

Abstract: We aimed to review tools used to assess balance in clinical practice in children and adults with cerebral palsy (CP), to describe their content and measurement properties and to evaluate the quality of the studies that have examined these properties. CINAHL, Embase, and PubMed/MEDLINE were searched. The COnsensus-based Standards for selection of health Measurement INstruments (COSMIN) was used to assess the 'quality of studies' and the Terwee criteria were used to assess the 'result of studies'. Twenty-two cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
123
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 80 publications
2
123
1
2
Order By: Relevance
“…Health professionals were contacted from (1) the CPL and CP Alliance through the organization's representative; (2) members of the AusACPDM (nonmedical AusACPDM members, eg, lawyers or parents, were not contacted); and (3) authors of research articles about postural control who were identified in recent systematic reviews [8][9][10] and who have published contact details. Potential participants numbered approximately 711, based on the number of invitations disseminated (fig 1).…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Health professionals were contacted from (1) the CPL and CP Alliance through the organization's representative; (2) members of the AusACPDM (nonmedical AusACPDM members, eg, lawyers or parents, were not contacted); and (3) authors of research articles about postural control who were identified in recent systematic reviews [8][9][10] and who have published contact details. Potential participants numbered approximately 711, based on the number of invitations disseminated (fig 1).…”
Section: Participantsmentioning
confidence: 99%
“…Respondents who submitted Round 1 also gave consent to participate in subsequent rounds. Round 1 contained open-ended questions constructed by the authors (box 1) based on theoretical principles of postural control and systematic reviews of postural control assessments, 8,9 interventions, 10 and approaches. 10 The questions sought responses for postural control (1) definitions; (2) framework for development, assessment, and intervention; (3) assessments; and (4) interventions for children with CP.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 3 more Smart Citations